Culturally Grounded Counseling for Resilience: Validating a Tri Hita Karana-Based Scale Using the Rasch Model - Suastini, Ni Wayan (KONSELOR, 2025)
This study investigates how to include of Tri Hita Karana values—Parahyangan (spiritual), Pawongan (social), and Palemahan (environmental)—into school-based guidance and counselling services and their role in enhancing student resilience. The study utilised a quantitative methodology and Rasch model analysis, involving 229 high school students in Bali who had undergone counselling services. The instrument was created utilising the Tri Hita Karana framework and resilience theory, and was verified with Winsteps software. The analysis results reveal significant student appreciation for all three value dimensions, with male students demonstrating particularly robust integration. The scale had robust psychometric features (person reliability = 0.86; item reliability = 0.84) and satisfied the unidimensionality criterion as determined by Principal Component Analysis of Residuals (PCAR). The Wright Map demonstrated a distinct variation in students' levels of value internalisation, allowing counsellors to recognise individuals with diminished engagement and formulate targeted therapies centred on specific domains—Parahyangan, Pawongan, or Palemahan. These findings underscore the significance of culturally rooted values in improving the efficacy and contextual pertinence of guiding and counselling procedures within multicultural educational environments.